Correlation between EFL Students’ Language Aptitude and their English Proficiency - Kartini Tobroni; Farah Natchiar Mohd Khaja (Universitas Bengkulu, 2021)
This study is designed to investigate the correlation between EFL students’ language aptitude and their English proficiency. The data were collected from sixty-five students in the end of their eighth semester at the English department in faculty of teacher training in UIN Raden Fatah Palembang.The students took a foreign language aptitude test(both explicit and implicit LLAMA tests) and an English proficiency test (TOEFL). The collected data was analyzed using Pearson-Product Moment correlation test. It reveals that Pearson correlation between LLAMA explicit scores and TOEFL scores is significant at 0.676, P < 0.01 (2-tailed), so the correlation between LLAMA explicit scores and TOEFL scores is considered moderate. In addition, the correlation between LLAMA implicit scores and TOEFL scores is significant at 0.422, P < 0.01 (2-tailed), therefore, the correlation between LLAMA implicit scores and TOEFL scores is considered low.